The Theoretical Foundations of the Emergence of Subversive Ideas in the Family and the Promotion of Countermeasures (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This scientific work analyzes the causes and social-psychological factors behind the emergence of subversive ideas within the family and explores the theoretical and propagandistic foundations for countering them. In the context of globalization and the rapid advancement of information technologies, various ideological movements are widely disseminated through the Internet, penetrating the family environment — the most essential unit of society. As a result, negative influences that contradict moral and spiritual values increasingly affect young minds, leading to significant shifts in worldview and behavior. The study investigates the nature and spread of subversive ideas, their manifestation within family relationships, and their influence on youth consciousness. The family, being the environment in which a person’s moral integrity, beliefs, and ideological immunity are formed, serves as a primary institution in the prevention of destructive ideologies. Therefore, creating a healthy ideological atmosphere within the family, strengthening mutual trust and moral dialogue between parents and children, and developing information literacy are emphasized as key preventive measures.As effective strategies to resist subversive ideas, this paper highlights the importance of promoting national ideology and moral education, fostering patriotism, humanism, and social responsibility among youth. Moreover, the study examines the role of the state, public organizations, mass media, and educational institutions in advocacy and awareness campaigns.